The Effect of Electroconvulsive Therapy (ECT) on the Ability to Control Violent Behavior in the Gatotkaca Ward, Dr. Amino Gondohutomo Mental Hospital, Central Java Province - Yulina Mahaling; Dwi Indah Iswanti (BIOSAINSTEK, 2026)
Violent Behavior is an acts of aggression or violent behavior manifested verbally, physically, or via both modalities towards a target, individual, or oneself. Signs and symptoms such as red and tense face, glaring/sharp gaze, clenched fists, pacing, and high tone of voice (Pardede, J. A., & Laila, B. 2020). This study aims to implement and evaluate nursing intervention SP 1 (Deep breathing and pillow hitting technique) and the administration of Electroconvulsive Therapy (ECT) among patients displaying within the Gatotkaca Inpatient Unit of RSJD Dr. Amino Gondohutomo, Central Java Province. The approach method us utilized in this investigation is a case study design violent behavior employing a descriptive technique (Nursalam, 2020). The participants in this research consisted of three patients dealing with violent behavior issues within the Gatotkaca Inpatient Unit of RSJD Dr. Amino Gondohutomo, Central Java Province. This study showed no significant effect when administering Deep Breathing and Pillow Hitting before administering Electroconvulsive Therapy (ECT) and there was a significant impact on patients undergoing scheduled electroconvulsive therapy, with changes in physical and verbal behavior compared to before scheduled electroconvulsive therapy. There was no variation regarding the control of violent behavior within the three patients preceding electroconvulsive therapy (ECT), and a notable shift occurred in the control of violent behavior among the three patients subsequent to electroconvulsive therapy (ECT). This measure may be utilized as a substitute therapy in psychiatric nursing practice.